18. OUTCOME ASSESSMENT OF DECOMPRESSIVE CRANIECTOMY FOR TRAUMATIC BRAIN INJURY AT THONG NHAT HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the treatment outcomes for patients with traumatic brain injury undergoing decompressive craniectomy at Thong Nhat Hospital.Methods: A cross-sectional retrospective study was conducted on patients with traumatic brain injury indicated for decompressive craniectomy from January 2017 to January 2020 at Thong Nhat Hospital.Results: We surveyed and followed 172 patients who met the inclusion criteria, with the following outcomes: At the time of discharge/transfer, the proportion of patients with a favorable outcome (Glasgow Outcome Scale [GOS] 4 and 5) was 69.18%, and those with an unfavorable outcome (GOS 1, 2, and 3) was 30.82%. Of these, 115 patients (66.86%) had a Glasgow Coma Scale (GCS) score of 14 to 15, and 31 patients (18.02%) had a GCS score of 9 to 13. Complications that affected patient outcomes after decompressive craniectomy included recurrent hemorrhage, accounting for 50.58%, and several factors such as intraventricular hemorrhage, basal cistern compression were associated with the formation of new postoperative hematoma influencing the patients' outcome.Conclusion: Decompressive craniectomy (DC) is a time-tested method commonly applied in emergency situations to save the lives of patients after accidents. To accurately assess the effectiveness of this surgery, it is essential to consider clinical, radiological, and potential risk factors to select the most appropriate surgical timing to achieve ideal outcomes, facilitating not only surgery but also swift patient recovery and reintegration into everyday life.
Keywords: Decompressive craniectomy; traumatic brain injury; intraventricular hemorrhage; hematoma and brain contusion/swelling